The Effect of Promotion, Online Customer Reviews, and Rating Perceptions on the Decision to Use the Tokopedia Application: Evidence from Surabaya, Indonesia - Adhara, Linc Bellatrix; Supriyono, S. (Manunggal Halim Jaya, 2026)
This study analyzes the influence of promotion, online customer reviews, and customer rating perception on users' decisions to use the Tokopedia application in Surabaya. The research addresses a gap in previous studies that have not explicitly focused on Tokopedia users in this region. A quantitative research method was employed using a survey approach. Data were collected from 105 Tokopedia users in Surabaya through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that all three independent variables, promotion, online customer review, and online customer rating perception, positively and significantly impact the decision to use the Tokopedia application. These findings highlight the importance of digital promotions, credible user reviews, and high user ratings in influencing consumer decisions. Tokopedia is encouraged to optimize its digital marketing and online reputation management strategies to enhance user trust, retention, and competitive advantage in the Indonesian e-commerce market.